Dimensionamento de sistema híbrido para suprimento de serviços auxiliares em subestações de transmissão - Weyh, Cássio Hallmann (My University, 2026)
The substations are fundamental components inside of Brazilian electrical system, because they shelter equipments like circuit breakers, disconnect switches and transformers, which play functions such as electrical protection, power flow direction and voltage level suitability of the diverse parts of the system. Those equipments have power components, connected to high voltage, and control components, that work in low voltage and are supplied by those named auxiliary services. When it comes to transmission system substations, the auxiliary systems should have redundant sources, independent and reliable, according to the National System Operator (ONS) settings, which could be from the substation itself, from local concessionary, or even from an alternative sourcing, to be evaluated by the agency, in case of previous applications not to be possible. Some substations which auxiliary services are supplied by the local concessionary are located far from consumption centers, where sourcing levels are lower than those set by the National Electricity Agency (ANEEL), performing an unreliable source for the auxiliary services. Thus, in this composition it was done an analysis of technical feasibility for using hybrid sources of distributed generation (DG), being composed by a photovoltaic generation system (PVGS) and a battery energy storage system (BESS) , for auxiliary services supply with no concessionary dependency, but which will make use of it to inject the exceeding generated energy, allowing the energy credits compensation through the remote self-consumption mode, previewed in the law 14.300/2022, legal mark of distributed microgeneration and minigeneration. The technical feasibility of using these supply systems happened from the commercial options checking, as so of photovoltaic generation systems as of batteries energy storage systems, and their simulation with the software OpenDSS, being verified: by the PVGS, the system supply capacity even in the worst condition of generation (critical month) and the amount of energy injected into the concessionary source during an annual cycle; by the BESS, the charging supply capacity during a minimum period of time without batteries recharging and, still, the continuous charging supply, with diary discharge/recharge cycles, condition which it was analyzed the relationship between discharging depth and the life cycle of the batteries. [resumo fornecido pelo autor]
As subestações (SEs) são componentes fundamentais dentro do sistema elétrico brasileiro, pois abrigam equipamentos como disjuntores, chaves seccionadoras e transformadores, que desempenham funções como proteção elétrica, direcionamento do fluxo de potência e adequação dos níveis de tensão das diversas partes do sistema. Esses equipamentos possuem componentes de potência, ligados à alta tensão, e componentes de comando, que funcionam em baixa tensão e são supridos pelos chamados serviços auxiliares (SAs). Nas SEs de transmissão, os SAs devem possuir fontes redundantes, independentes e confiáveis, conforme estabelecido pelo Operador Nacional do Sistema (ONS), que podem ser oriundas da própria SE, da concessionária local ou, ainda, de um fornecimento alternativo, a ser avaliado pelo órgão, em caso de impossibilidade da aplicação das anteriores. Algumas SEs que possuem suprimento da concessionária para os SAs localizam-se distantes dos centros de consumo, onde os níveis de fornecimento são inferiores aos estabelecidos pela Agência Nacional de Energia Elétrica (ANEEL), configurando-se como uma fonte não confiável para os SAs. Dessa forma, neste trabalho foi realizada a análise de viabilidade técnica da utilização de fontes híbridas de geração distribuída (GD), compostas por sistema de geração fotovoltaica (SGFV) e sistema de armazenamento de energia em baterias (SAEB), para suprimento dos SAs sem depender da concessionária, mas que se utilizarão desta para injeção do excedente de geração, permitindo a compensação de créditos de energia na modalidade de autoconsumo remoto, prevista na lei 14.300/2022, marco legal da microgeração e minigeração distribuída. A viabilidade técnica da utilização destes sistemas de suprimento se deu a partir da verificação de opções comerciais, tanto de SGFV quanto de SAEB, e sua simulação no software OpenDSS, verificando: por parte do SGFV, a capacidade de suprimento do sistema mesmo na pior condição de geração (mês crítico) e o montante de energia injetado na rede da concessionária em um ciclo anual; por parte do SAEB, a capacidade de suprimento da carga por um período mínimo sem recarga das baterias e, ainda, o suprimento contínuo da carga, com ciclos diários de descarga/recarga das baterias, condição em que foi analisada a relação entre profundidade de descarga e ciclo de vida destas. [resumo fornecido pelo autor]
Keywords: Engenharia elétrica; Subestações elétricas; Geração distribuida de energia elétrica; Sistemas de energia fotovoltaica; Energia - Armazenamento